Impulsivity, online disinhibition, and risk taking among digital millennials: challenges of e-Safety in Industry 4.0 - Erfianti, Levina Gendis; Mohd Mahudin, Nor Diana (National Institute of Occupational Safety and Health (NIOSH), 2019)
Digital Millennials (i.e., people born from 1980 to 2004) have often been portrayed as quick to embrace emerging technologies. The envisioned future of Industry 4.0 entails the blending of hardware, software, and people to complete work; and given their affinity for digital resources, technology, and social networking applications, the Millennials could be regarded as a much-needed asset in this future workforce. However, systematic research on how this cohort understands and reacts to safety issues surrounding the use of technologies has been lacking. In particular, behaviours such as impulsivity, online disinhibition, and risk-taking among them remain unclear. The present study investigated this gap with a sample of 203 Millennials of various nationality groups. Using the short version of the Urgency, Premeditation, Perseverance, Sensation Seeking, and Positive Urgency (Short UPPS-P) scale, the Revised Online Disinhibition Scale, and the Online Risky Behaviour scale, the results indicated that the most significant predictors of online risk-taking behaviours are lack of premeditation, positive urgency, and toxic disinhibition. Interestingly, though not hypothesised, was gender as a significant predictor of the outcome. The findings implied that these variables might be the most relevant target areas for interventions that could modify risky behaviours in cyberspace. The study’s findings are discussed in relation to the key challenges associated with e-safety where the future trends would be heading towards the gig economy and crowd-working.